Recognition and Mentoring Program Miftahul ‘Ula Intensif Technopreneurship Carrer: Menumbuhkembangkan Inventor dan Inovator Santripreneur - Satia Nur Maharani; Zainul Abidini (Jurnal Pengabdian UntukMu NegeRI, 2022)
The Islamic Education Institute (LPI) Miftahul 'Ula Islamic Boarding School produces students who have entrepreneurial competencies by directly involving all students from high school to university level to turn on and manage LPI's economic activities. However, this economic potential has not been fully utilized. Direct observation of economic resource management activities at LPI Miftahul 'Ula shows that academic and non-academic programs in the field of entrepreneurship are less than optimal. Therefore, in the community service program for the Community Partnership Program, the proposing team helps solve problems through workshops, training programs and mentoring programs for the Recognition and Mentoring Program: Miftahul 'Ula Intensive Technopreneurship Carrer. Intensive programs start from basic technopreneurship, Invention and Innovation Development, Impact Creation and Evaluation to psychological aspects to cultivate a strong and healthy entrepreneurial spirit. The results of the implementation of the activity showed an increase in the competence and capability of the technopreneurship of students, one of the indicators is the ability to design and prepare business plans for the use of technology.